SMEs Record Keeping in Ghana: Has VAT Made It Better? - Adom, Philip Kofi; Amakye, Kwaku; Doh, Edinam; Anku, Regina (International Journal of Economics and Financial Issues, 2013)
With the introduction of the VAT Flat Rate Scheme, which brings on-board traders on whom the VAT record-keeping requirements would or might prove burdensome, concerns arise on the potential impact of the ‘VAT record keeping requirement’ on SME’s record keeping. The focus of this study was to investigate the effect of the record-based controls of VAT on firms’ record keeping skills and accounting system based on a sample of 250 SME’s selected from five key trading centres in the Accra metropolis. The result showed that completion of the VAT monthly return form imposes more cost on traders than the VAT invoice book. Firms who receive education from VAT officials are found to be 0.102 more likely to complete the VAT monthly return form than firms who do not receive education from VAT officials. Also, firms who receive education from VAT officials are 0.849 times as likely as those firms who had not received education from VAT officials to complete the VAT invoice book by self. Generally the result showed that the ‘record-based controls of VAT’ has significantly improved SME’s record keeping skills and accounting system albeit it is found to be stringent relative to other record keeping types kept by SME’s. Keywords: Record-based control of VAT; SMEs; Ghana; Survey research design JEL Classifications: H00; H2; H25; H32